THU0054 The Lung Microbiome in Rheumatoid Arthritis and Local/Systemic Autoimmunity. (9th June 2015) - Scher, J.; Ubeda, C.; Segal, L.; Vijay, J.; Artacho, A.; Catrina, A.
Abstract : Background: Rheumatoid arthritis (RA) is a complex, autoimmune disease in which several genetic and environmental factors play a role. Recent data suggest that the gut and oral microbiome might potentially contribute to an aberrant systemic immune response characteristic of RA. Among recently studied microbiota, both P. gingivalis in the oral cavity 1 and P. copri 2 in the gut have been implicated. Imaging abnormalities seen in RA patients and also in at-risk individuals for the development of disease 3 along with the presence of autoantibodies in the airways 4 implicates the lung as yet another site of autoimmunity generation in RA. Objectives: To test whether the RA lung microbiome contains distinct taxonomic features that associate with local and/or systemic autoimmunity Methods: Bronchoalveolar lavage (BAL) samples from 20 subjects with RA and 10 with sarcoidosis were obtained by research bronchoscopy. 16S rDNA sequencing was performed to define microbiota composition. Levels of arginine/citrulline were measured in BAL fluid using GC-MS for all samples. Autoantibodies, including anti-CCP, RF and ACPAs were also measured in RA subjects in BAL and serum. Statistical analysis was performed using wilcoxon test and Spearman correlation. Results: There were no differences in demographic or clinical characteristics (including smoking status) between the groups. 16S sequencing data show similar alpha and beta diversity based on UniFrac between groups. Taxonomic comparison between RA and sarcoidosis was performed using LEfSe, which revealed several significant differences (LDA score>2). While RA BAL samples were enriched with Sphingobacteria, sarcoidosis BAL was enriched with Bacteroidia, Rhizobiales, Nitrospirales, and Campylobacter . GC-MS showed similar levels of arginine and citrulline in BAL for the sarcoidosis and RA groups. Raoultella and Barnesiella correlated with CCP2 levels in BAL (rho=0.49 and 0.47; p-value=0.026 and 0.032 respectively). Serum levels of CCP-IgA had a negative correlation with Massilia and Tannerella (rho= -0.63 and 0.53; p-value 0.003 and 0.016, respectively), and a positive correlation with Vagococcus and Lactobacillus (rho=0.59 and 0.54; p-value 0.006 and 0.014, respectively). Unclas_Lactobacillales also had a positive correlation with serum levels of RF-IgA (rho=0.71; p-value <0.001). Serum levels of anti-CCP2 antibodies had a negative correlation with Escherichia and Bdellovibrio (rho=-0.47 and 0.45, p-value=0.03 and 0.04 respectively), and a positive correlation with Porphyromonas, Rahnella and Chryseobacterium (rho=0.46, 0.46 and 0.45; p-value=0.03, 0.03 and 0.04 respectively). Conclusions: Despite the relatively small number of samples analyzed, several taxonomic differences were noted between RA and Sarcoidosis. Correlations between relative abundance of specific taxa in BAL with serum autoantibodies (i.e., anti-CCP) support an association between the lung microbiome and the host immune phenotype in RA. Further evaluation of functional aspects of this microbiome may provide further insights into its possible contribution to RA. References: Scher JU, Arthritis Rheum. 2012;64(10):3083-94. Scher JU, Elife. 2013 Nov 5;2:e01202. Willis VC, et al., Arthritis Rheum. 2013;65(10):2545-54. Reynisdottir G, et al., Arthritis Rheumatol. 2014;66(1):31-9 Disclosure of Interest: None declared